Evaluation of Iron Levels in Newborns with HIE - Ali, Irfan (Biological and Clinical Sciences Research Journal, 2025)
Neonatal hypoxic-ischemic encephalopathy (HIE) is a major cause of mortality and neurodevelopmental disability, particularly in low-resource settings. Iron metabolism may be disrupted in HIE due to oxidative stress and inflammation, potentially affecting neurological outcomes. Objective: To evaluate serum iron levels in newborns with HIE and investigate their association with disease severity and clinical outcomes. Methods: This descriptive cross-sectional study was conducted at Department of Neonatal Medicine, Sindh institute of Child Health and Neonatology Korangi-5, Karachi, July, 2024 to December, 2024. Eighty term neonates with HIE (Sarnat staging) were enrolled within 72 hours of life. Serum iron, ferritin, and total iron-binding capacity (TIBC) were measured, and their relationship with HIE severity and Apgar scores was analyzed using SPSS version 25. Results: Neonates with severe HIE (Stage III) had significantly lower serum iron (59.1 ± 11.4 µg/dL) and ferritin levels, and higher TIBC compared to milder stages (p < 0.01). Lower Apgar scores correlated with reduced iron levels. Conclusion: Severe HIE is associated with altered iron metabolism, suggesting a potential role for iron as a biomarker. Cautious iron management may improve outcomes, warranting further research.